Yet another decennium of the Institute of Physiology: a dynamic interplay of innovative approaches and 60 years of tradition - Kubínová, L (Physiological research, 2014)
I am pleased to introduce this special issue of Physiological Research published on the occasion of the 60th anniversary of the Institute of Physiology. It is only a second issue of this kind, the previous one being Physiological Research 53 (Suppl. 1) 2004. Since then, the Institute contributed its expertise to modern fields of physiology such as cardiovascular physiology, neurophysiology, energy metabolism, membrane transport, chronobiology, as well as relevant methodology. Diverse local and international collaboration has augmented such effort, as summarized in the attached Synopsis outlining the most significant achievements of Institute's departments during the past ten years. I very much hope that achievements of this kind will become Institute's tradition justifying at least equally optimistic forthcoming special issues in the decades to come.
Keywords: Academies and Institutes; periodika jako téma; Publishing; výročí a významné události; Physiology; Periodicals as Topic; Animals; Humans; lidé; fyziologie; zvířata; Physiological Phenomena; publikování; fyziologické jevy; akademie a ústavy; Anniversaries and Special Events